Implementation of Human Resources Management in Improving the Quality of Education in SDN No 35 Maccini Baji Takalar Regency - Iswanto Najamuddin (Journal AGENCY, 2023)
This research aims to find out how the process of implementing human resource management improves the quality of education at SDN NO 35 Maccini Baji, Takalar Regency. This type of research is field research carried out by meeting respondents or informants directly. The data collection technique used to obtain valid data is through observation, interviews and documentation taken directly from informants, namely the principal and teachers of SDN NO 35 Maccini Baji, Takalar Regency. The data analysis techniques used are through data reduction, data presentation and drawing conclusions and verification. The results of the findings of this research are that the implementation of management in improving the quality of education is going well and is quite adequate, the implementation of human resource management at SDN No. 35 Maccini Baji goes through several stages (1) Carrying out an effective human resource planning process. (2) Carry out external recruitment through the education office and internal recruitment and selection for additional staff such as honorary teachers. (3) Placing employees according to interests and talents. (4) Holding training so that the skills of teachers and employees increase (5) Carrying out performance assessments within one semester. (6) Provide appreciation in the form of compensation and bonuses according to position and qualifications. (7) Terminate employment relations in accordance with mutual agreement. Meanwhile, improving the quality of education is carried out using input, process and output indicators in management. The input indicators are increasing teacher professionalism, the process of carrying out the recruitment process through promotions and improving facilities and infrastructure and the output indicators are academic and non-academic achievements.